Elucidation of hydrolysis reaction mechanism of tungsten hexafluoride (WF6) using first-principles calculations - Jung, Hyunwook; Hwang, Jeemin; Chun, Hoje; Han, Byungchan (Journal of industrial and engineering chemistry (Seoul, Korea), 2019)
Free energy diagram of the hydrolysis of WF6 and its reaction intermediates has been calculated using first-principles density functional theory calculation. [Display omitted] •First-principles study on the hydrolysis of WF6 and its intermediates.•Tungsten fluorides and water form stable adduct, which is labile to ligand substitution.•Hydrolysis of WOF4 is the bottleneck of the overall process. We identify hydrolysis reaction mechanism of water-reactive WF6 and its accompanying intermediates using first-principles calculations. For the purpose, we evaluate activation and free energy diagrams of elementary reaction steps. We find that WF6, WOF4, and WO2F2 form stable adducts, which quickly reacts with H2O by substituting the ligand F. Gaseous WOF4, WO2F2, WO3 are predicted as unstable in the increasing order, but polymerization reduces their instability, leading to solidification. In overall reaction, WOF4 hydrolysis is the bottleneck due to significantly higher activation barrier of trans isomeric complex than cis counterpart.